Endovascular management of an aortic rupture following transcatheter aortic valve replacement - Omran, Nedal; Kvasnak, Martin; Derner, Milos; Cervinka, Pavel (Journal of cardiac surgery, 2018)
We report a case of aortic rupture during transcatheter aortic valve replacement (TAVR) managed successfully by urgent stent-graft implantation.
Keywords: Aortic Rupture; Treatment Outcome; Aged; aorta thoracica; Female; Endovascular Procedures; senioři; Humans; Imaging, Three-Dimensional; Stents; Tomography, X-Ray Computed; výsledek terapie; počítačová rentgenová tomografie; pooperační komplikace; Ambulatory Care; ruptura aorty; ambulantní péče; lidé; Postoperative Complications; ženské pohlaví; transkatetrální implantace aortální chlopně; Aorta, Thoracic; endovaskulární výkony; zobrazování trojrozměrné; stenty; Transcatheter Aortic Valve Replacement